2013
DOI: 10.3109/08039488.2013.814711
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia in patients with conversion disorder

Abstract: The level of alexithymia in conversion disorder patients, without any other psychiatric disorder, is higher than that of the healthy controls. During the evaluation of the psychological state of patients with conversion disorder, it could be useful to keep in mind the probability of them having alexithymia to determine the type of suitable therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
1
16
1
1
Order By: Relevance
“…29 Only one study has assessed alexithymia in other functional disorders. 18 This study differs from ours in several important ways: they grouped together all types of functional neurological disorder, they used a single comparison group of healthy controls and they did not assess comorbidities. Nevertheless, they too found a higher rate of alexithymia in patients than controls, although this was higher than ours (74.5%), and they also found that this pertained to the DIF and DDF factors only.…”
Section: Discussion Alexithymiamentioning
confidence: 99%
See 1 more Smart Citation
“…29 Only one study has assessed alexithymia in other functional disorders. 18 This study differs from ours in several important ways: they grouped together all types of functional neurological disorder, they used a single comparison group of healthy controls and they did not assess comorbidities. Nevertheless, they too found a higher rate of alexithymia in patients than controls, although this was higher than ours (74.5%), and they also found that this pertained to the DIF and DDF factors only.…”
Section: Discussion Alexithymiamentioning
confidence: 99%
“…As additional evidence for this interpretation, patients with FMS were not significantly different from controls In the last few years, several studies have examined the relationship between alexithymia and functional neurological symptoms, mainly focusing on NESs. The most common finding is that patients with NESs are no more likely to have alexithymia than patients with epileptic seizures; [16][17][18][19][20][21][22][23][24][25][26][27] one study has found an increased prevalence in NES, 28 although another suggests that emotional dysregulation, including alexithymia, may pertain to a small subgroup. 29 Only one study has assessed alexithymia in other functional disorders.…”
Section: Discussion Alexithymiamentioning
confidence: 99%
“…Alexithymia, the deficient ability to perceive and verbally express emotions [25], signifies another correspondence between DD and PTSD. As representative of altered affect regulation alexithymia has been shown in DD patients [26–29], as well as in PTSD patients [30]. Frewen and colleagues reported positive correlations between alexithymia, PTSD symptom severity, dissociative symptom severity, and childhood abuse and neglect in PTSD patients, while Sondergaard and Theorell [31] determined evolving alexithymia as predictor of self-rated PTSD (but not depressive) symptoms in refugees.…”
Section: Introductionmentioning
confidence: 99%
“…Alexithymia construct emerged on the ground of psychosomatic medicine, after observation of emotional functioning of patients suffering from psychosomatic diseases, who due to lack of understanding of their emotional state were preoccupied by physical symptoms [49]. However, recent studies show that alexithymia, which is understood as a psychological trait [50] and measured by Toronto Alexithymia Scale, developed by Bagby, Parker, and Taylor [51] is not specific for only one mental disorder, but also for conversion [52], major depression, social anxiety disorder [53], panic disorder, generalized anxiety disorder [54], anorexia nervosa and bulimia nervosa [55]. Alexithymia was found to be correlated with gambling [29] -one of self-regulatory lapses.…”
Section: Adaptive and Maladaptive Aspects Of Affect Regulationmentioning
confidence: 99%